2017
DOI: 10.1261/rna.061655.117
|View full text |Cite
|
Sign up to set email alerts
|

Conformational dynamics of the frameshift stimulatory structure in HIV-1

Abstract: Programmed ribosomal frameshifting (PRF) in HIV-1 is thought to be stimulated by a hairpin in the mRNA, although a pseudoknot-like triplex has also been proposed. Because the conformational dynamics of the stimulatory structure under tension applied by the ribosomal helicase during translation may play an important role in PRF, we used optical tweezers to apply tension to the HIV stimulatory structure and monitor its unfolding and refolding dynamics. The folding and unfolding kinetics and energy landscape of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 65 publications
8
30
0
Order By: Relevance
“…In contrast, \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}${{attC}}_{{\rm{bs}}}^{}$\end{document} and \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}${{\ attC}}_{{\rm{ts}}}^{}$\end{document} hairpins unfold at lower forces (<6 pN) via two consecutive events and show evidence of complex folding dynamics involving on-pathway intermediates. The partial unfolding of the hairpins into intermediate states (step 1, Figure 2E) occurred mostly at forces lower than the detection limit, similar to a recently reported case for the HIV-1 RNA hairpin with an unstable lower stem (28,29) or DNA hairpins with single base damages like 8-oxoguanine (30). The major unfolding event for attC hairpins was typically at forces around 5.5 pN.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}${{attC}}_{{\rm{bs}}}^{}$\end{document} and \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{upgreek} \usepackage{mathrsfs} \setlength{\oddsidemargin}{-69pt} \begin{document} }{}${{\ attC}}_{{\rm{ts}}}^{}$\end{document} hairpins unfold at lower forces (<6 pN) via two consecutive events and show evidence of complex folding dynamics involving on-pathway intermediates. The partial unfolding of the hairpins into intermediate states (step 1, Figure 2E) occurred mostly at forces lower than the detection limit, similar to a recently reported case for the HIV-1 RNA hairpin with an unstable lower stem (28,29) or DNA hairpins with single base damages like 8-oxoguanine (30). The major unfolding event for attC hairpins was typically at forces around 5.5 pN.…”
Section: Discussionsupporting
confidence: 86%
“…Do downstream stimulatory structures play active or passive roles in directing recoding? Numerous studies suggest that dynamic mRNA structural remodeling helps to physically “push” ribosomes to slip (Ritchie et al 2012; Tinoco et al 2013; Gupta and Bansal 2014; Ritchie et al 2014; Moomau et al 2016; Tsai et al 2016; Zhong et al 2016; Kendra et al 2017; Ritchie et al 2017). Coordination of base triples in both major and minor grooves provide mechanical resistance to pseudoknot unwinding, and stretches of adenosines confined along the minor groove of a helix prevent it from unwinding.…”
Section: Translational Recodingmentioning
confidence: 99%
“…However, a survey of numerous different pseudoknots showed that the mechanical resistance was uncorrelated to −1 PRF efficiency; instead, −1 PRF efficiency was found to correlate with conformational plasticity or heterogeneity (16). This correlation was supported by subsequent work extending SMFS studies of −1 PRF to other pseudoknots (30), different types of stimulatory structures such as hairpins (31), and the effects of antiframeshifting ligands (32). Evidence supporting the importance of conformational plasticity has also been found from single-molecule fluorescence experiments of ribosomes translocating through pseudoknots (33) and ensemble structural studies of stimulatory structures using such methods as selective 2′-hydroxyl acylation analyzed by primer extension (SHAPE) (21,34).…”
mentioning
confidence: 97%